Relationship Between Working Capital and Profitability (A Case Study of Dr. Reddy’s Laboratories Limited) - Rastogi, S. K; Kumar, Durgesh (Journal of Commerce and Trade, 2018)
Maintaining the smooth and continuous flow of business is the challenging task for each organization, for this management needs the availability of each and every component of four M i.e. Man, Machine, Money and Material. Routine management of these four components is known as “Working Capital Management”. Working capital management is an important task for any business house as it maintains the uninterrupted flow. Decisions relating to the working capital are taken on each day based on the circumstances. Working capital is very important component of corporate finance because it directly affects the liquidity and profitability of the company. Working capital is the base for any organization especially for manufacturing organization. Management of Dr. Reddey’s Laboratories Limited has maintained a better relationship between Working Capital and Profitability during the study period of ten years 2007-08 to 2016-17. Researchers have used Financial Ratios for the present study as well as some very important statistical tools such as Karl Pearson Correlation, Spearman Rank Correlation, Regression Analysis, One Way Anova Test. Motaals Test is also used to determine the liquidity and profitability score. Classification-JEL : G 11, L 22, M 31.